The Effectiveness of Simulation Game Based Group Counseling in Enhancing Students’ Emotional Regulation - Aldea Putri Rahmawati; Siti Fitriana; Padmi Dhyah Yulianti (Indonesian Journal of Learning Education and Counseling, 2026)
This study focuses on examining the effectiveness of group counseling services utilizing simulation game techniques in managing the emotions of tenth-grade students at SMA Negeri 1 Mranggen. The intervention consisted of group counseling sessions employing simulation games, conducted over five meetings with a duration of 40 minutes per session. The measured indicators included self-awareness, self-regulation, motivation, empathy, and social skills. Methodologically, this study employed a quantitative approach with a one-group pretest-posttest experimental design. 10 students were selected as subjects through simple random sampling, utilizing a 29-item Likert scale instrument that had been tested for validity and reliability. Based on the results of the t-test, there was an increase in scores for each participant as well as across all emotional management indicators, indicating a significant difference between conditions before and after the intervention.